Comparison of Transcutaneous Electrical Nerve Stimulation and Parasternal Block for Postoperative Pain Management after Cardiac Surgery - Ozturk, Nilgun Kavrut (Pain Res Manag, 2016)
Background. Parasternal block and transcutaneous electrical nerve stimulation (TENS) have been demonstrated to produce effective analgesia and reduce postoperative opioid requirements in patients undergoing cardiac surgery. Objectives. To compare the effectiveness of TENS and parasternal block on early postoperative pain after cardiac surgery. Methods. One hundred twenty patients undergoing cardiac surgery were enrolled in the present randomized, controlled prospective study. Patients were assigned to three treatment groups: parasternal block, intermittent TENS application, or a control group. Results. Pain scores recorded 4 h, 5 h, 6 h, 7 h, and 8 h postoperatively were lower in the parasternal block group than in the TENS and control groups. Total morphine consumption was also lower in the parasternal block group than in the TENS and control groups. It was also significantly lower in the TENS group than in the control group. There were no statistical differences among the groups regarding the extubation time, rescue analgesic medication, length of intensive care unit stay, or length of hospital stay. Conclusions. Parasternal block was more effective than TENS in the management of early postoperative pain and the reduction of opioid requirements in patients who underwent cardiac surgery through median sternotomy. This trial is registered with Clinicaltrials.gov number NCT02725229.